Perspectives on New Testament Textual Criticism: Collected Essays, 1962–2004. By Eldon Jay Epp. Pp. xl + 856. (Supplements to Novum Testamentum, 116.) Leiden: Brill, 2005. isbn 90 04 14246 0. €178/238 - Foster, Paul (The journal of theological studies, 2006)
The contribution of Eldon Epp to the discipline of New Testament textual criticism over the last five decades has resulted in studies that have been wide-ranging and programmatic, and whose impact has reshaped approaches to the manuscript evidence. Perhaps still best known for his 1966 monograph The Theological Tendency of Codex Bezae Cantabrigiensis in Acts, Epp convincingly demonstrated in that volume that Codex Bezae was theologically motivated in introducing ‘a clearly anti-Judaic tendency in the D-text of Acts’ (p. 171). Apart from this study, Epp's scholarly output has appeared in the form of detailed (and often quite lengthy) articles, rather than in further monographs (although his new book Junia: The First Woman Apostle is slated for publication in September 2005).